Adjuvant Chemotherapy for Stage II and III Colon Cancer Following Complete Resection: A Cancer Care Ontario Systematic Review. Issue 7 (July 2017) - Meyers, B.M.; Cosby, R.; Quereshy, F.; Jonker, D.
Abstract: The objective of this systematic review was to provide current evidence regarding the use of adjuvant systemic chemotherapy for stage II and III colon cancer following curative intent surgery. MEDLINE and EMBASE databases and proceedings of American Society for Clinical Oncology and European Society of Medical Oncology/European Cancer Congress were searched through to August 2015. Systematic reviews (with or without meta-analyses) and randomised controlled trials were included. Patients with completely resected stage III colon cancer have an overall survival benefit from adjuvant chemotherapy. Combination chemotherapy (5-fluorouracil/leucovorin/oxaliplatin or capecitabine/oxaliplatin) provides a larger benefit than monotherapy but with additional toxicity. For stage II colon cancer, a clear overall survival benefit has not been shown. However, based on the subgroup analysis available, patients with high-risk stage II disease may benefit from adjuvant chemotherapy. Patients younger than 70 years of age may derive greater disease-free survival and overall survival benefit from adjuvant chemotherapy (in combination with oxaliplatin) compared with those older than 70 years. Stage II patients with microsatellite instability may have an overall survival detriment if given adjuvant chemotherapy.